Studi Literatur: Pengaruh Pembelajaran Flipped Classroom Terhadap Hasil Belajar Matematika Siswa - Nurfalah, Edy; Ansori, Muhammad Miftahur Rizal (FKIP Unirow Tuban, 2024)
Flipped classroom learning has become an increasingly popular educational innovation, especially in the context of mathematics education. This article aims to systematically review the existing literature on the effectiveness of the flipped classroom model in improving mathematics concept understanding skills among students. Through this review, we identify the approaches, advantages, challenges and learning outcomes produced by the flipped classroom method. The results of the review indicate that flipped classroom learning has significant potential in improving mathematical concept understanding, although there are some challenges that need to be addressed in its implementation.